Effectiveness and functionality of small group reading instruction for at-risks learners: A convergent parallel study - Rizalina P. Costales (S&Co Publishing, 2026)
This mixed-methods convergent parallel study examined the effectiveness and functionality of small group reading instruction for 120 at-risk Grade 2 learners across 12 public elementary schools in Bauang North District, Philippines. Quantitative findings revealed statistically significant improvements (p<0.001) across all reading components following the intervention, with large effect sizes for word recognition (d=1.17) and reading comprehension (d=1.09), and a moderate-to-large effect for reading fluency (d=0.93). Qualitative analysis of teacher interviews (n=12) identified three key themes regarding functionality: reconfiguring participation from passive to tentative engagement, instruction as diagnostic practice enabling targeted support, and functionality as negotiated practice requiring continuous adaptation to time constraints, classroom management demands, and resource limitations. Challenges included insufficient instructional time, managing multiple groups simultaneously, lack of leveled reading materials, and navigating learner diversity. The convergence of findings demonstrates that small group reading instruction is both effective in improving reading proficiency and conditionally functional within real-world classroom contexts. However, effectiveness is not inherent to the strategy alone but emerges through teacher agency, contextual adaptation, and the negotiation of structural constraints. The study advances a dual-dimension framework emphasizing that instructional interventions must be understood not only in terms of measurable outcomes but also through their practical enactment, with implications for theory, policy, and practice in resource-constrained educational settings.